Conformation and microenvironment of the active site of a low molecular weight 1,4-beta-D-glucan glucanohydrolase from an alkalothermophilic thermomonospora sp.: involvement of lysine and cysteine residues - Jagtap, Sharmili; Rao, Mala (Biochemical and Biophysical Research Communications, 2006)
Conformation and microenvironment at the active site of 1,4-beta-D-glucan glucanohydrolase was probed with fluorescent chemo-affinity labeling using o-phthalaldehyde. OPTA has been known to form a fluorescent isoindole derivative by cross-linking the proximal thiol and amino groups of cysteine and lysine. Modification of lysine of the enzyme by TNBS and of cysteine residue by PHMB abolished the ability of the enzyme to form an isoindole derivative with OPTA. Kinetic analysis of the TNBS and PHMB-modified enzyme suggested the presence of essential lysine and cysteine residues, respectively, at the active site of the enzyme. The substrate protection of the enzyme with carboxymethylcellulose (CMC) confirmed the involvement of lysine and cysteine residues in the active site of the enzyme. Multiple sequence alignment of peptides obtained by tryptic digestion of the enzyme showed cysteine is one of the conserved amino acids corroborating the chemical modification studies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 1; 4-beta-D-glucan glucanohydrolase; active site microenvironment; Cysteine; lysine; OPTA; PHMB; Thermomonospora sp.; TNBS

Biochemical characterization of a novel beta-1-3, 1-4 glucan 4-glucanohydrolase from thermomonospora sp having a single active site for lichenan and xylan - Anish, Ramakrishnan; Rao, Mala (Biochimie, 2007)
A bifunctional high molecular weight (Mr, 64,500 Da) beta-1-3, 1-4 glucan 4-glucanohydrolase was purified to homogeneity from Thermomonospora sp., exhibiting activity towards lichenan and xylan. A kinetic method was used to analyze the active site that hydrolyzes lichenan and xylan. The experimental data was in agreement with the theoretical values calculated for a single active site. Probing the conformation and microenvironment at active site of the enzyme by fluorescent chemo-affinity label, OPTA resulted in the formation of an isoindole derivative with complete inactivation of the enzyme to hydrolyse both lichenan and xylan confirmed the results of kinetic method. OPTA forms an isoindole derivative by cross-linking the proximal thiol and amino groups. The modification of cysteine and lysine residues by DTNB and TNBS respectively abolished the ability of the enzyme to form an isoindole derivative with OPTA, indicating the participation of cysteine and lysine in the formation of isoindole complex. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1-4 glucan 4-glucanohydrolase; beta-1-3; bifunctional; O-phthaialdehyde; single active site; Thermomonospora sp.; Xylanase

Encapsulation of endoglucanase using a biopolymer Gum arabic for its controlled release - Ramakrishnan, Anish; Pandit, Nilesh; Badgujar, Mahesh; Bhaskar, C.; Rao, Mala (Bioresource Technology, 2007)
{Gum Arabic, a biodegradable natural polymer was used as a matrix to encapsulate endoglucanase from Thermomonospora sp. The modified enzyme retained complete biocatalytic activity and exhibited a shift in the optimum temperature [
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

Glycine-assisted enhancement of 1,4-beta-D-xylan xylanohydrolase activity at alkaline pH with a pH optimum shift - Vathipadiekal, Vinod; Verma, Anamika; Rao, Mala (Biological Chemistry, 2007)
This is the first report describing the enhancement of xylanase activity by the neutral amino acid glycine. Xylanase activity is increased seven-fold at alkaline pH in the presence of glycine and its pH optimum is shifted from pH 7 to 8 without using any protein engineering techniques. Analysis of the steady-state kinetics revealed that glycine in the reaction mixture increases the K-m and k(cat) values of the enzyme. Chemoaffinity labeling and studies using glycine esters indicate an involvement of the carboxylate ion of glycine in enhancing xylanase catalytic activity. A novel possible mechanism for the glycine-assisted catalytic action of xylanase is proposed.
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase